The complete chloroplast genome sequence of Xylosma racemosa (Siebold & Zucc.) Miq. (Salicaceae). Issue 10 (3rd October 2021) - Tong, Lili; Tian, Lu; Xu, Xiaogang; Xia, Chongli; Cheng, Yao; Jiang, Xiaoyu; Wang, Hongchao; Tian, Yukun
Abstract: Xylosma racemosa (Siebold & Zucc.) Miq. which plays an important role in ecology, medicine and economy, is a deciduous species of Salicaceae. In this paper, we sequenced, assembled, and annotated the chloroplast (cp) genome of X . racemosa (Siebold & Zucc.) Miq. by using the sequencing data from Illumina Novaseq platform. The complete cp genome of X. racemosa is 157, 262 bp in length, containing a large single-copy (LSC) region of 84, 289 bp, and a small single-copy (SSC) region of 17, 817 bp. It contains 131 genes, including 8 rRNA genes, 37 tRNAs genes and 86 protein-coding genes. The GC content of X. racemosa cp genome is 36.74%. The phylogenetic analysis suggests that X. racemosa is a sister species to Xylosma congesta in Salicaceae.